2007
DOI: 10.1038/sj.gene.6364382
|View full text |Cite
|
Sign up to set email alerts
|

Human interferon lambda-1 (IFN-λ1/IL-29) modulates the Th1/Th2 response

Abstract: Interferon lambda-1 (IFN-l1/IL-29) is a member of the Type-III interferon family, which contains three ligands: IFN-l1, 2 and 3. These three ligands use the same unique heterodimeric receptor composed of CRF2-12 (IFN-l-R1/IL-28Ra) and CRF2-4 (IL10-R-b) chains. Like their close relatives, the Type-I interferons, IFN-l1, 2 and 3, promote the phosphorylation of STAT1 and STAT2, induce the ISRE3 complex, elevate OAS and MxA expression and exhibit antiviral activity in vitro. Their use of the IL10-R-b chain and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
177
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 66 publications
7
177
1
3
Order By: Relevance
“…We confirmed the broad expression pattern of the IFNAR system, and found that among the cell types examined, that pDCs were the only hemopoietic cell type that responded to IFN-. Others have reported that human monocytes, blood monocyte-derived DCs, and murine intrahepatic CD3 Ϫ DX5 ϩ NK cells respond to IFN-or express the receptor chains (28,29,47,49). Therefore, we conclude that only few cell types of the hemopoietic compartment are responsive to IFN-, although we cannot exclude that expression of the type III IFN receptor system may be induced by cell differentiation and activation in a broader spectrum of cells.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We confirmed the broad expression pattern of the IFNAR system, and found that among the cell types examined, that pDCs were the only hemopoietic cell type that responded to IFN-. Others have reported that human monocytes, blood monocyte-derived DCs, and murine intrahepatic CD3 Ϫ DX5 ϩ NK cells respond to IFN-or express the receptor chains (28,29,47,49). Therefore, we conclude that only few cell types of the hemopoietic compartment are responsive to IFN-, although we cannot exclude that expression of the type III IFN receptor system may be induced by cell differentiation and activation in a broader spectrum of cells.…”
Section: Discussionmentioning
confidence: 51%
“…For instance, treatment with IFN-1 induces expression of a subset of inflammatory cytokines in human monocytes and macrophages (47,48). Others have reported that human blood monocytes gain responsiveness to IFNduring differentiation to DCs, and that these DCs induce proliferation of regulatory T cells (29) and modulation of the Th1/Th2 response (49). In a different study it was shown that intrahepatic CD3 Ϫ DX5 ϩ NK cells express the IFN-receptor chains and contribute to the antitumor activities of IFN- (28).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these investigations, some studies did propose direct effects of IFN-ls on monocytes, 32,33 DCs 34 and T cells. [35][36][37][38][39][40] We currently cannot explain the discrepancy in these observations in terms of whether IFN-ls influence, for example, monocytes or T cells. As we demonstrated, it seems that the preactivation with cell-specific stimuli or virus-mimicking agents could not confer any clear responsiveness to these cytokines on peripheral immune cells.…”
Section: Discussionmentioning
confidence: 74%
“…These effects can be direct on CD4 + T cells or indirect, via MDDC. Further, IFN-l1 secretion is itself Th2 cytokine responsive (11,12,(21)(22)(23). Recent studies also showed that IFN-l1 expression is reduced in alveolar macrophages and bronchial epithelial cells of rhinovirus-infected asthmatic individuals (24,25).…”
mentioning
confidence: 96%